2012
DOI: 10.3892/or.2012.1743
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of sphingosine kinase isoforms ablates TNF-induced drug resistance

Abstract: Recent research has demonstrated that aberrant sphingolipid signaling is an important mechanism of chemo-resistance in solid tumors. Sphingosine kinase (Sphk), the primary enzyme metabolizing the sphingolipid ceramide into sphingosine-1-phosphate (S1P), is a primary mediator of breast cancer promotion, survival and chemoresistance. However, to date the mechanism of Sphk-mediated drug resistance is poorly understood. Using the dual sphingosine kinase isozyme inhibitor, SKI-II (4-[4-(4-chloro-phenyl)-thiazol-2-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…However, there are multiple indications that sphingolipid-signalling modulating agents have potent therapeutic efficacy against cancer. For instance, tamoxifen sensitivity is restored by inhibiting SphK1 signalling (Sukocheva et al 2009), which has also been shown for other chemotherapeutic drugs including doxorubicin (Antoon et al 2012). We are now only starting to understand how sphingolipids coordinate the multiple mitogenic signals leading to neoplastic cell growth and cancer development.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, there are multiple indications that sphingolipid-signalling modulating agents have potent therapeutic efficacy against cancer. For instance, tamoxifen sensitivity is restored by inhibiting SphK1 signalling (Sukocheva et al 2009), which has also been shown for other chemotherapeutic drugs including doxorubicin (Antoon et al 2012). We are now only starting to understand how sphingolipids coordinate the multiple mitogenic signals leading to neoplastic cell growth and cancer development.…”
Section: Discussionmentioning
confidence: 88%
“…According to Montagut et al (2006), chemoresistance correlated well with NF-kB activation in tumour specimens from breast cancer patients. Interestingly, pharmacological inhibition of SphK blocks NF-kB transcriptional activation and induces the intrinsic apoptosis pathway in multi-drug-resistant BCCs (Antoon et al 2012). The SphK inhibitor ABC294640 diminished NF-kB survival signalling, through decreased phosphorylation of Ser536 on the p65 subunit.…”
Section: Studies With Sphk Inhibitors and S1p Receptor Agonistsmentioning
confidence: 99%
“…Inhibition of the Ras/ERK pathway in HepG2 human hepatoma cells using U0126 could sensitize them to SKI-II induced cell death [251]. In combination with doxorubicin or etoposide, SKI-II can increase the percentage of dead MCF-7TN-R cells [252]. SKI-II treatment of MDA-MB-231, HCT-116 colon cancer and NCI-H358 lung cancer cells increased sensitivity to doxorubicin treatment and formation of reactive oxygen species [253].…”
Section: Part 4 Inhibitors Of Sk1 and Their Applicationmentioning
confidence: 99%
“…TNF resistance was generated by prolonged and progressive exposure of MCF-7 cells to TNF to produce the isogenic MCF-7TN-R cell system. These MCF-7TN-R cells exhibited complete resistance to TNF-induced cell death, with exposure to TNF resulting in increased phosphorylated, but not total levels of downstream NF-κB signaling202122. We have previously demonstrated that these cells do not generate intracellular ceramide, a well known marker of chemoresistance in response to chemotherapeutic treatment192324.…”
mentioning
confidence: 97%